Odpowiedź:
[tex]a)\ \ \dfrac{1}{\sqrt{3}}=\dfrac{1}{\sqrt{3}}\cdot\dfrac{\sqrt{3}}{\sqrt{3}}=\dfrac{\sqrt{3} }{3}\\\\\\b)\ \ \dfrac{10}{\sqrt{2}}=\dfrac{10}{\sqrt{2}}\cdot\dfrac{\sqrt{2}}{\sqrt{2}}=\dfrac{\not10^5\sqrt{2}}{\not2_{1}}=5\sqrt{2}\\\\\\c)\ \ \dfrac{1}{\sqrt[3]{3}}=\dfrac{1}{\sqrt[3]{3}}\cdot\dfrac{\sqrt[3]{3^2}}{\sqrt[3]{3^2}}=\dfrac{\sqrt[3]{3^2}}{\sqrt[3]{3\cdot3^2}}=\dfrac{\sqrt[3]{9}}{\sqrt[3]{3^{1+2}}}=\dfrac{\sqrt[3]{9}}{\sqrt[3]{3^3}}=\dfrac{\sqrt[3]{9}}{3}[/tex]
[tex]d)\ \ \dfrac{8}{\sqrt[3]{4}}=\dfrac{8}{\sqrt[3]{2^2}}\cdot\dfrac{\sqrt[3]{2}}{\sqrt[3]{2}}=\dfrac{8\sqrt[3]{2}}{\sqrt[3]{2^2}\cdot\sqrt[3]{2}}=\dfrac{8\sqrt[3]{2}}{\sqrt[3]{2^2\cdot2}}=\dfrac{8\sqrt[3]{2}}{\sqrt[3]{2^{2+1}}}=\dfrac{8\sqrt[3]{2}}{\sqrt[3]{2^3}}=\dfrac{\not8^4\sqrt[3]{2}}{\not2_{1}}=4\sqrt[3]{2}[/tex]